Cost Utility Analysis Vildagliptin dan Glimepiride dalam Mencegah Komplikasi Mikrovaskuler menggunakan Model Markov - Purnamasari, Tri Julia; Ilone, Stella; Setiawan, Didik (Faculty of Pharmacy, Universitas Gadjah Mada, 2023)
Microvascular complications can occur due to type 2 diabetes mellitus (DM). The cost of therapy increases due to the use of various antidiabetic drugs over a long period. This research is a pharmacoeconomic study that uses the Markov Model to compare costs and utilities in type 2 DM patients who receive metformin+glimepiride and metformin+vildagliptin therapy. Primary data was collected through the EQ5D questionnaire at Cirebon Harbor Hospital and secondary data (transition probability) was collected through a literature study. Characteristics of type 2 DM patients show that the majority of people suffering from this condition are aged between 55 and 59 years. Primary data from the hospital shows that the cost of therapy for controlled type 2 DM patients who receive combination therapy of metformin + glimepiride, and metformin + vildagliptin is Rp. 1,699,400, Rp. 5,807,786, and Rp. 10,100,426, respectively. Secondary data from articles treating type 2 DM shows that the 55-59 year age group is the largest. With an ICER of 61,493,943/QALYS, microvascular prevention in T2DM patients receiving the metformin+vildagliptin combination in Indonesia is considered effective and able to reduce the number of microvascular cases. This is based on the ICER value compared to the Indonesian Government's GDP, namely Rp. 71,030,183.3. This study shows that replacing glimepiride with vildagliptin for the prevention of microvascular complications is cost-effective and has better utility and effectiveness in reducing the incidence of microvascular complications. The use of vildagliptin can be recommended to reduce costs and the risk of microvascular complications.